2009
DOI: 10.1021/es802661p
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Reprogramming and Estrogenic Sensitization in Wild Fish Exposed to Ethinylestradiol

Abstract: Globally, feminization responses in wild male freshwater fish are caused by exposure to estrogenic chemicals, including natural and synthetic estrogens, contained in effluents from wastewater treatment works. In U.K. rivers, feminization responses, including intersex, are widespread in wild roach (Rutilus rutilus) populations, and severely affected fish have a reduced reproductive success. We exposed roach to environmentally relevant concentrations of the contraceptive estrogen 17Rethinylestradiol (EE 2 ) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
116
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 53 publications
2
116
1
Order By: Relevance
“…0960-0760/$ -see front matter © 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.jsbmb.2010.11.015 roach inhabiting UK rivers have shown that exposure to estrogenic effluents emanating from wastewater treatment works (WwTWs 3 ) caused altered sexual development that can resulted in reduced fertility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…0960-0760/$ -see front matter © 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.jsbmb.2010.11.015 roach inhabiting UK rivers have shown that exposure to estrogenic effluents emanating from wastewater treatment works (WwTWs 3 ) caused altered sexual development that can resulted in reduced fertility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A study looking at the concentration of EE 2 in shorthead redhorse suckers (Moxostoma macrolepidotum) collected near a wastewater treatment plant also confirmed EE 2 as a probable candidate for bioaccumulation (Al-Ansari et al, 2010). EE 2 is an estrogen receptor agonist and exposure is a major environmental concern due to its ability to induce estrogenic effects at low concentrations (> 10 ng/L) (Kidd et al, 2007;Lange et al, 2009;Parrott & Blunt, 2005). Many studies have looked at the effects of EE 2 on fish fecundity in both laboratory and field settings.…”
Section: Figurementioning
confidence: 98%
“…They found that after seven years, a near extirpation of the species had occurred due to an inhibition of spawning (Kidd et al, 2007). A decrease in GSI and an altered ovarian structure is another welldocumented effect of EE 2 exposure that has been observed in the fathead minnow (Kidd et al, 2007), the wild roach (Rutilus rutilus) (Lange et al, 2009), rare minnow (Gobiocypris rarus) (Zha, Wang, Wang, & Ingersoll, 2007) and the zebrafish (Van den Belt et al, 2002). Several studies have shown that zebrafish are sensitive to the effects of EE 2 which are mediated by impacts on a variety of reproductive pathways (Segner et al, 2003).…”
Section: Figurementioning
confidence: 98%
“…Correlations between intersex fish and EDCs have been observed in several studies (Harris et al, 2011;Kidd et al, 2007;Lange et al, 2009;Puy-Azurmendi et al, 2013) and are characterized by the presence of vitellogenin in the blood of male fish and the presence of oocytes and/or female reproductive ducts (oviducts) in male fish testes (Bahamonde et al, 2013;Harris et al, 2011;Jobling et al, 2006). Feminized fish fertility is generally reduced and consequently the contribution of these fish to the growth rate of the population is likely to be reduced (Harris et al, 2011;Jobling et al, 2006;Kidd et al, 2007).…”
Section: Introductionmentioning
confidence: 95%